Cloprostenol sodium improves reproductive performance of multiparous sows during lactation - Zhu, Xuedan; Zhang, Xinke; Zhang, Yuqing; Li, Jiahao; Li, Siqi; Zhang, Siqi; Li, Li; Meng, Li; Wei, Hengxi; Zhang, Shouquan (Frontiers in Veterinary Science, 2024)
This study aimed to determine the effect of prostaglandin F2α analogs (D-cloprostenol sodium and DL-cloprostenol sodium) administration on the milk yield of multiparous sows (MS) and piglet growth performance. In total, 320 Landrace×Yorkshire parturient MS were randomly divided into 3 groups on day 115 of pregnancy: without treatment, with 75 μg D-cloprostenol sodium and with 200 μg DL-cloprostenol sodium. After delivery, the sows treated with D- and DL-cloprostenol sodium were randomly allocated into three subgroups respectively: i) no additional treatment; ii) administration of cloprostenol sodium at 3 h and 5 d after farrowing, respectively, and iii) administration of cloprostenol sodium at 3 h, 5 d and 10 d after farrowing, respectively. Cloprostenol sodium effectively induced sows to synchronize parturition approximately 23 h after administration and increased the daytime delivery rates (P < 0.05). Compared with DL-cloprostenol sodium, D-cloprostenol sodium shortened the farrowing duration and birth interval of sows for inducing farrowing (P < 0.05). Moreover, we observed that a single administration of cloprostenol sodium a day before delivery significantly reduced the rates of stillborn piglets type Ⅱ (P < 0.05). Compared to no treatment and single treatment with cloprostenol sodium, quartic treatments with cloprostenol sodium significantly increased the daily feed intake of MS, litter weight weaned and average daily gain of piglets (P < 0.05). Cloprostenol sodium improved 21-days milk yield, with Dcloprostenol sodium showing the best effect, which increased lactation ability by 30.30 % (176.72 kg vs. 135.63 kg) (P < 0.05). DL-cloprostenol sodium followed closely, increasing lactation ability by approximately 25.00 % (P < 0.05). During lactation, sows administered with D-cloprostenol sodium observed increased serum prolactin levels. Compared to untreated sows, the sows administred with D-cloprostenol sodium and multiple DL-cloprostenol sodium visibly shortened weaning-to-estrus interval and weaning-to-service interval (P < 0.05). Furthermore, quartic injections of D-cloprostenol sodium resulted in an 18 percentage point increase in pregnancy rate of breeding sows compared to control (P > 0.05); In summary, cloprostenol sodium could enhance the reproductive performance of MS, particularly in terms of lactation performance. Additionally, the effect of quartic injections of D-cloprostenol sodium was most pronounced.